Empirical investigation of purchasing power parity for Turkey: Evidence from recent nonlinear unit root tests - Dilem Yildirim (Central Bank Review (CBR), 2017)
This study explores the empirical validity of the purchasing power parity (PPP) hypothesis between Turkey and its four major trading partners, the European Union, Russia, China and the US. Accounting for the nonlinear nature of real exchange rates, we employ a battery of recently developed nonlinear unit root tests. Our empirical results reveal that nonlinear unit root tests deliver stronger evidence in favour of the PPP hypothesis when compared to the conventional unit root tests only if nonlinearities in real exchange rates are correctly specified. Furthermore, it emerges from our findings that the real exchange rates of the countries having a free trade agreement are more likely to behave as linear stationary processes.
Keywords: 330; Purchasing power parity; Real exchange rate; Nonlinearity; Smooth transition Turkey